2020
DOI: 10.22146/mot.45955
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Phyllanthus niruri and Sonchus arvensis as Components of Scientific Jamu

Abstract: Saintifikasi Jamu, or the scientific investigation of Jamu, is an evidence-based process to ensure the safety and efficacy of herbal medicine through health service research. Jamu has been empirically explored as a composition of various crude drugs, hence called as Scientific Jamu. Phyllanthus niruri and Sonchus arvensis are two of the 30 medicinal plants processed into Scientific Jamu. Components of the Scientific Jamu are standardized to ensure that these materials meet the predefined quality. This study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A lower water content results in the growth of less mold, fungus, and enzymatic reactions that can degrade the product's quality. 23 The bulbs contain 0.53% total ash, 0.28% acid-insoluble ash, and 0.29% water-soluble ash, as shown in Table 4. The higher the total ash content obtained, the higher the mineral content contained in the simplicia.…”
Section: Pharmacognostic Studymentioning
confidence: 99%
“…A lower water content results in the growth of less mold, fungus, and enzymatic reactions that can degrade the product's quality. 23 The bulbs contain 0.53% total ash, 0.28% acid-insoluble ash, and 0.29% water-soluble ash, as shown in Table 4. The higher the total ash content obtained, the higher the mineral content contained in the simplicia.…”
Section: Pharmacognostic Studymentioning
confidence: 99%
“…Various studies showed that P. niruri contains flavonoids, alkaloids, tannins, polyphenols, saponins, terpenoids, and lignans [7,8]. Some studies have also shown differences in the phytochemical content from different growing conditions, processing methods, and harvest times [2,9]. While several studies have substantiated the advantageous properties of P. niruri extract, the outcomes obtained exhibit notable variability.…”
Section: Introductionmentioning
confidence: 99%
“…The development and advancement of technology are currently attracting the attention of several researchers, especially in the field of natural product development, to develop several plants as medicine to support public health 1 . The community has long used natural materials as an empirical medicine to treat several diseases 2 . Indonesian traditional medicinal plants are increasingly used as standardized traditional medicines and phytopharmacology.…”
Section: Introductionmentioning
confidence: 99%